2011
DOI: 10.1111/j.1742-4658.2011.08030.x
|View full text |Cite
|
Sign up to set email alerts
|

Dmrt1 genes at the crossroads: a widespread and central class of sexual development factors in fish

Abstract: A plethora of corroborative genetic studies led to the view that, across the animal kingdom, the gene‐regulatory cascades triggering sexual development bear little resemblance to each other. As a result, the common emerging picture is that the genes at the top of the cascade are not conserved, whereas the downstream genes have homologues in a much broader spectrum of species. Among these downstream effectors, a gene family involved in sex differentiation in organisms as phylogenetically divergent as corals, Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
119
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(126 citation statements)
references
References 59 publications
6
119
1
Order By: Relevance
“…Dmrt1 (dsx and mab-3 related transcription factor 1) is a member of a gene family of putative transcription factors that share a highly conserved DNA binding domain (DM domain) believed to play critical roles in testis development and differentiation of vertebrates (Herpin and Schartl, 2011;Masuyama et al, 2012;Xia et al, 2007;Zarkower, 2013). Several sex determination and sex chromosome-linked genes in vertebrates such as Dmy in medaka (Matsuda et al, 2002;Nanda et al, 2002), DM-W in the W chromosome of African clawed frog (Yoshimoto et al, 2008), and Dmrt1 in the Z chromosome of birds (Smith et al, 2009), have been shown to be recently duplicated homologs of Dmrt1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dmrt1 (dsx and mab-3 related transcription factor 1) is a member of a gene family of putative transcription factors that share a highly conserved DNA binding domain (DM domain) believed to play critical roles in testis development and differentiation of vertebrates (Herpin and Schartl, 2011;Masuyama et al, 2012;Xia et al, 2007;Zarkower, 2013). Several sex determination and sex chromosome-linked genes in vertebrates such as Dmy in medaka (Matsuda et al, 2002;Nanda et al, 2002), DM-W in the W chromosome of African clawed frog (Yoshimoto et al, 2008), and Dmrt1 in the Z chromosome of birds (Smith et al, 2009), have been shown to be recently duplicated homologs of Dmrt1.…”
Section: Introductionmentioning
confidence: 99%
“…Several sex determination and sex chromosome-linked genes in vertebrates such as Dmy in medaka (Matsuda et al, 2002;Nanda et al, 2002), DM-W in the W chromosome of African clawed frog (Yoshimoto et al, 2008), and Dmrt1 in the Z chromosome of birds (Smith et al, 2009), have been shown to be recently duplicated homologs of Dmrt1. Because of the high evolutionary conservation and the newly recruited role in vertebrates (Herpin and Schartl, 2011;Xia et al, 2007), Dmrt1 also allows us to analyze the evolutionary history of genome duplication through examination of divergence and phylogeny of the duplicated genes. In this study, we analyzed Dmrt1 genes of polyploid gibel carp and closely related species to reveal genetic evidence for supporting hypotheses of the polyploidy origins.…”
Section: Introductionmentioning
confidence: 99%
“…4 and 5). Previously, the expressed DMRT1 was reported to be present in all of about 20 examined teleost fish species and to correlate with testis development, but the Dmrt1 expressed cells were found to be various (Herpin and Schartl, 2011;Zarkower, 2013), such as only in Sertoli cells , both in Sertoli and germ cells (Lei et al, 2007), or only in germ cells (Xia et al, 2007). In this study, we have clearly captured the cell types of Dmrt1 expression in testes, the Sertoli cells and spermatogenic cells.…”
Section: Discussionmentioning
confidence: 58%
“…Increasing evidences have indicated that most of the known sex determination genes discovered so far in vertebrates are derived from the duplicated homologs of Dmrt1 gene (Chong et al, 2013;Gamble and Zarkower, 2012;Gempe and Beye, 2011;Graves, 2013;Herpin and Schartl, 2011;Kikuchi and Hamaguchi, 2013;Matson and Zarkower, 2012;Siegal and Baker, 2005;Zhou and Gui, 2010). For gibel carp, as a unisexual lineage that is able to utilize gynogenesis as a unisexual reproduction mode, how male individuals arise and how male determination genes evolve will be the merit for further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation